Penerapan Konsep Sadd Al-Dzari’ah pada Fenomena Hubungan Tanpa Komitmen (Friends With Benefit/FWB): Upaya Pencegahan Terhadap Pelanggaran Moralitas Islam - Orvin Adyatma Eka; Muthoifin, Muthoifin (proceedings.icesy, 2026)
Abstract From the perspective of Islamic law, the phenomenon of friends with benefits (FWB) is not merely a matter of social freedom, but a legal issue that directly intersects with the principle of Hifdzun Nasl and the violation of the boundaries of Sadd al-Dzari’ah. This study aims to analyze the FWB phenomenon as part of modern social dynamics, examine the limits of interaction according to Islamic law, and the legal and moral implications it raises. The research method used is normative law with a case and concept approach, and it examines sources of Islamic law. The research findings indicate that the practice of FWB is fundamentally contrary to the principles of Islamic law, which considers marriage as the only legitimate mechanism for sexual relations. Islamic law not only prohibits adultery as a final act but also forbids all forms of interaction and social relationships that lead to adultery, as emphasized in the concepts of sadd al-dzari’ah and maqasid al-shariah, particularly the protection of honor and lineage. Thus, this phenomenon is a moral and legal deviation that has the potential to cause social harm